Spitz Nevus with Features of Clark Nevus, So-Called SPARK Nevus: Case Series Presentation with Emphasis on Cytological and Histological Features - Antonietta Cimmino; Gerardo Cazzato; Anna Colagrande; Eugenio Maiorano; Lucia Lospalluti; Giuseppe Ingravallo; Leonardo Resta (MDPI AG, 2021)
Background: SPARK nevus represents a little-known and characterized entity, with few case series available in the literature. Methods and results: we present a case series of 12 patients (6 F and 6 M) between January 2005 and December 2020 and conduct a review of the current literature. Ten articles were selected on the basis of the adopted inclusion criteria and the PRISMA guidelines. Conclusions: The definition of histopathological and dermoscopic criteria are important to allow for an agreement to be reached among dermopathologists, and for the development of a consensus on higher case studies. To our knowledge, there are not many case series in the literature, and ours is part of the attempt to increase the knowledge of an entity that remains little-known and characterized.